Cristais de cloridrato de éster metílico de L-tirosina e L-cisteína: estudo DFT, caracterização térmica, eletrônica, estrutural e vibracional sob diferentes pressões - SILVA, Ronaldo (2024)
Proteinogenic amino acids constitute proteins via peptide bonds. Post-translational modifications of proteins, such as methylation, are a mechanism for genetic code variability and cellular physiology regulation. Thus, the main purpose of this work was to study, using various characterizations (electronic, spectroscopic, structural, thermal, and vibrational), the hydrochlorides of methylated amino acids: L-Cysteine Methyl Ester Hydrochloride (LCMEHCl) and L-Tyrosine Methyl Ester Hydrochloride (LTMEHCl), as a function of pressure and/or temperature, with emphasis on Raman Spectroscopy results. For this objective, the following characterizations were performed: structural by X-Ray Diffraction using the Powder Method and Rietveld Refinement; spectroscopic and vibrational by Raman Spectroscopy (as a function of pressure from 0.0 to 9.0 GPa) and Fourier Transform Infrared Spectroscopy (FTIR) under room conditions (298 K and 1 atm); electronic (Calculation of Frontier Molecular Orbitals – Highest Occupied Molecular Orbital (HOMO) and Lowest Unoccupied Molecular Orbital (LUMO), determination of chemical reactivity indices and Hirshfeld Surfaces, de, di, dNorm. and 2D-fingerprint); thermal characterization by Thermogravimetric Analysis (TGA), Derivative Thermogravimetric Analysis (DTG), Differential Thermal Analysis (DTA) and Differential Scanning Calorimetry (DSC). Computational calculations based on Density Functional Theory (DFT) were performed: with cam-B3LYP and wB97x-D3 functionals and Def2-TZVP basis set (to calculations for the molecules) or LDA-PZ functional (to calculation for the unit cell). Crystals of LCMEHCl and LTMEHCl were obtained with orthorhombic and monoclinic crystal systems and space groups P212121 (D2 4 ) and P21 (C2 2 ), respectively. Additionally, the parameters Rp, Rwp, and S for LCMEHCl were 6.88%, 9.33%, and 1.27, while, for LTMEHCl, they were 6.65%, 9.5%, and 1.48. High-pressure Raman spectroscopy results indicated that LCMEHCl and LTMEHCl possibly undergo continuous reversible conformational modifications within the pressure ranges: 0.0-0.7 GPa and 0.7-4.2 GPa for LCMEHCl, and 0.3-1.3 GPa and 2.8-6.0 GPa for LTMEHCl (with possibly phase transitions between 0.5-0.7 GPa and 3.8-4.2 GPa for LCMEHCl; around 1.0 and 6.0 GPa for LTMEHCl). The results suggest that the methylated amino acids, in this study, seem to have greater flexibility and lower stability than their non- methylated analogues, probably due to the influence of methylation, the aromatic ring, and the thiol group on the chemical interactions of LCMEHCl and LTMEHCl.